Pharmacological Strategies for Enhanced Recovery after General Surgery, Assessing the Efficacy and Safety of NSAIDs, Opioids, and Adjuncts - RASHID, MUHAMMAD; SHAH, MUHAMMAD TAIMOOR; KAUSAR, SALMA (Pakistan Journal of Medical & Health Sciences, 2025)
Background: Enhanced Recovery after Surgery (ERAS) protocols implement multimodal strategies aiming to improve the postoperative outcomes and to reduce the complications. Pharmacological pain management with NSAIDs, opioids and adjunctive agents is a major component, but comparative data on efficacy and safety are lacking for the most part in general surgical settings. Aim: To assess and compare the efficacy and safety of NSAIDs, opioids and adjunct analgesics on improving postoperative recovery in patients undergoing general surgical procedures. Methodology: It was a prospective comparative study on 79 patients who were undergoing elective general surgery. The patients were grouped into three groups based on the postoperative analgesia given: Group A (n=27 with NSAIDs, Group B (n=26 with opioids) and Group C (n=26 with adjuncts, such as paracetamol and gabapentinoids). Outcomes measured included pain scores (Visual Analog Scale), time to first ambulation, return of bowel function, length of hospital stay and adverse events such as nausea, renal impairment, respiratory depression, or gastrointestinal bleeding. Result: NSAIDs provided good pain control and early bowel recovery with shorter hospital stay but had mild renal function alteration in 2 patients. The highest analgesia was noted in opioid recipients but there was a significantly higher frequency of nausea (23.1%) and delayed ambulation. The fewest side effects and moderate pain relief were seen with adjunct therapy, and good patient satisfaction, especially when used in a multimodal approach. Conclusions: NSAIDs and adjunct analgesics were favorable to opioids in recovery and safety among 79 surgical patients. These agents could be incorporated into a balanced multimodal regimen to optimize recovery in general surgical patients without increasing opioid related complications. These findings are further validated by further large scale trials.